1986
DOI: 10.1042/cs0710017
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory sensitivity to inhaled carbon dioxide around the control point during exercise

Abstract: Rapid steady-state CO2 responses were determined in five normal adults at rest and at up to six levels of exercise by injecting pure CO2 at a constant flow into the inspiratory limb of a breathing circuit. Ventilation (V) was measured with a dry gas meter and PCO2 at the mouth was recorded by a mass spectrometer. Mean alveolar PCO2 (PACO2) was taken as equal to end-tidal PCO2 at rest, and during exercise was derived graphically from the sloping alveolar plateaus. The accuracy of the latter method was checked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Together, these findings suggest that cerebrovascular responses during exercise, with or without accompanying elevated environmental temperature, are very different relative to that during passive heating. A number of studies have shown that, relative to resting conditions, ventilatory CO 2 sensitivity to a hypercapnic challenge (i.e., the change in ventilation in response to a change in PET CO 2 ) is increased during short-term aerobic exercise, independent of associated increases in core temperature (2,10,17,21,22,39). These studies support the hypothesis that exercise, independent of internal temperature, can alter responsiveness to CO 2 , although it is recognized that exercise-induced altered ventilatory responses to CO 2 are insufficient evidence to fully support the hypothesis that exercise itself can alter cerebrovascular responsiveness to CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that cerebrovascular responses during exercise, with or without accompanying elevated environmental temperature, are very different relative to that during passive heating. A number of studies have shown that, relative to resting conditions, ventilatory CO 2 sensitivity to a hypercapnic challenge (i.e., the change in ventilation in response to a change in PET CO 2 ) is increased during short-term aerobic exercise, independent of associated increases in core temperature (2,10,17,21,22,39). These studies support the hypothesis that exercise, independent of internal temperature, can alter responsiveness to CO 2 , although it is recognized that exercise-induced altered ventilatory responses to CO 2 are insufficient evidence to fully support the hypothesis that exercise itself can alter cerebrovascular responsiveness to CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…During exercise a graphical technique to calculate PAco2was simulated by the computer program. We have previously compared PA,Co2 obtained graphically with arterial CO2 (Pa,CO,) (Cummin et al 1986) and subsequently validated the computed version against the original manual technique (Jacobi et Figs 3 and 5). During exercise, the steady-state response was significantly higher than the transient at both flow rates.…”
Section: A)mentioning
confidence: 99%
“…The apparatus for the constant inflow technique is more fully described elsewhere (Cummin et al 1986;Jacobi et al 1987 a). Essentially, pure CO2 is run at accurately controlled rates into a small mixing chamber in the inspiratory line of a breathing circuit (Fig.…”
Section: Apparatusmentioning
confidence: 99%
“…On the other hand, Cummin, Alison, Jacobi, Iyawe & Saunders (1986), using CO2 administration, have reported an increased slope of the VE-alveolar PcO2 (PA, C02) relation close to the eucapnic point even in light exercise in euoxia. However, their timing of the crucial determinations was such as to straddle the peak of the early change of blood lactic acid (Cunningham & Douglas, 1987); such small transient changes of lactic acid during the early determinations would be capable of producing small lateral displacements of PA, c2' When the exercise intensity is well below the anaerobic threshold, as in the experiments to be reported here, the effects of any early rise of blood lactic acid have passed within about the initial 10 min.…”
Section: Introductionmentioning
confidence: 99%